Legal Analysis of Criminal Acts of Illegal Mining in Pidie Regency, Aceh (Analysis of Decision Number: 58/Pid.B/Lh/2022/Pn.Sgi) - Muhammad Chadafi, Said; Mandasari Saragih, Yasmirah (PT. Multidisciplinary Press Indonesia, 2024)
This article examines the legal criminal act of illegal mining that occurred in Pidie Regency, Aceh, with a focus on the analysis of Decision Number: 58/Pid.B/Lh/2022/Pn.Sgi. Illegal mining is a serious violation of environmental law and criminal law in Indonesia, due to its negative impacts on the ecosystem and the risks it poses to the local community. In this article, an analysis of the legal procedures applied in handling the case is carried out, starting from the investigation stage, prosecution, to the court decision. This study uses a qualitative approach with document analysis and case study methods, with data sources coming from court decisions, related laws and regulations, and academic literature. The results of the analysis show that in Decision Number: 58/Pid.B/Lh/2022/Pn.Sgi, there is an affirmation of the importance of permits in mining activities as well as strict sanctions for perpetrators who violate them. In addition, this article also reviews various factors that influence court decisions, including the evidence presented, the legal framework used, and the environmental impacts caused by illegal mining activities. In conclusion, this article emphasizes the importance of consistent law enforcement and strict supervision of mining activities, in order to prevent similar violations in the future and to maintain environmental sustainability in Aceh.